Dance between biology, mechanics, and structure: A systems‐based approach to developing osteoarthritis prevention strategies. Issue 7 (24th April 2015) - Chu, Constance R.; Andriacchi, Thomas P.
ABSTRACT Osteoarthritis (OA) is a leading cause of human suffering and disability for which disease‐modifying treatments are lacking. OA occurs through complex and dynamic interplays between diverse factors over long periods of time. The traditional research and clinical focus on OA, the end stage disease, obscured understanding pathogenesis prior to reaching a common pathway defined by pain and functional deficits, joint deformity, and radiographic changes. To emphasize disease modification and prevention, we describe a multi‐disciplinary systems‐based approach encompassing biology, mechanics, and structure to define pre‐osteoarthritic disease processes. Central to application of this model is the concept of "pre‐osteoarthritis, " conditions where clinical OA has not yet developed. Rather, joint homeostasis has been compromised and there are potentially reversible markers for heightened OA risk. Key messages from this perspective are (i) to focus research onto defining pre‐OA through identifying and validating biological, mechanical, and imaging markers of OA risk, (ii) to emphasize multi‐disciplinary approaches, and (iii) to propose that developing personalized interventions to address reversible markers of OA risk in healthy joints may be the key to prevention. Ultimately, a systems‐based analysis of OA pathogenesis shows potential to transform clinical practice by facilitating development and testing of new strategies to prevent or delay the onset of osteoarthritis. © 2015 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 33:939–947, 2015.